PENGARUH KEBIJAKAN PENGELOLAAN SDM DAN KESEJAHTERAAN TERHADAP PENINGKATAN KINERJA KARYAWAN PADA PT. ARISCO MANDIRI - Abdul Rohman; Fakhruddin Kurnia M (Universitas Ichsan Sidenreng Rappang, 2024)
The purpose of this research is to analyze the influence of human resource management (HRM) policies and employee welfare on improving employee performance at PT. Arisco Mandiri. Effective HRM policies and adequate welfare are important factors in enhancing productivity and work efficiency. This research uses a quantitative approach with a survey method. Data analysis is conducted using multiple linear regression to determine the relationship between these variables. The results show that HRM policies have a positive and significant influence on employee performance. Furthermore, employee welfare also contributes significantly to performance improvement. A combination of well-planned HRM policies and adequate welfare levels can create a conducive work environment, motivating employees to achieve company targets. The conclusion of this research is that HRM policies and employee welfare collectively have a significant influence on improving employee performance. Therefore, the company needs to increase its focus on these aspects to support organizational sustainability and growth.